Effect of noise on tasks in operating theatres: a survey of the perceptions of healthcare staff. Issue 2 (February 2017) - Padmakumar, A.D.; Cohen, O.; Churton, A.; Groves, J.B.; Mitchell, D.A.; Brennan, P.A.
Abstract: Noise in the operating theatre has an adverse impact on healthcare professionals, both physically and psychologically. It can be distracting, make communication difficult, and contribute to a perceived increase in stress. Staff in theatre must deliver high quality care, and overlook noise as a potentially damaging influence. The aim of this survey was to obtain further information about the perspective of healthcare professionals on how noise can affect their practice and whether it affects their work in theatre. We distributed six closed-ended questions in the form of a Survey Monkey ® questionnaire to about 50 hospitals across the UK and target groups such as medical students, the Leeds Advanced Trauma Life Support faculty group, the Court of Examiners of the Royal College of Surgeons of England, and surgical trainees sitting the Member of the Royal College of Surgeons examination. We received 519 responses of which 415 respondents (83%) thought that noise contributed to human errors. A total of 282 participants (57%) thought that the theatre was the noisiest area within the theatre suite. Both communication among staff (n = 400, 80%) and concentration (n = 384, 77%) were thought to be adversely affected by noise. However, 385 (78%) did not feel that music adversely affected their performance. The results provide insights into the interplay of noise and its effect on people. Although the role of music remains contentious, our results suggest that it might have a calming influence.